A Phase 1 First-Time-in-Human, Open-Label Study of Nelistotug Administered to Patients with Advanced Solid Tumors - Lillian L. Siu; Omid Hamid; Reva Schneider; Jordi Rodon. Ahnert; Scott A. Laurie; Frank Stephen. Hodi; Dong-Wan Kim; Myung-Ju Ahn; Gary Carlson; Hussein Assi; Hamza Khan; Patrick Hanafin; et al. (Clinical Cancer Research, 2026)
Abstract Purpose: This first-in-human, nonrandomized, multicenter study investigated nelistotug (anti-CD96 monoclonal antibody [mAb]) as monotherapy (Arm A) and in combination with dostarlimab (anti-PD-1 mAb) (Arm B), and dostarlimab plus belrestotug (anti-TIGIT mAb) (Arm F) in patients with recurrent or advanced solid tumors. Patients and Methods: Patients received intravenous doses every 3 weeks of nelistotug 2.1–1400 mg, nelistotug 70–1400 mg plus dostarlimab 500 mg, or nelistotug 1400 mg plus dostarlimab 500 mg plus belrestotug 400 mg in Arms A, B and F, respectively. Primary endpoints were dose-limiting toxicities (DLTs) and adverse events (AEs). Secondary endpoints included objective response rate, pharmacokinetics, and immunogenicity. Disease control rate and CD96 receptor occupancy were exploratory. Results: Thirty-six, 33, and 3 patients were included in Arms A, B, and F, respectively. No DLTs were observed in any arm, allowing for dose escalation to nelistotug maximum planned dose in Arms A and B, with a recommended phase 2 dose of 1400 mg. No treatment-related fatal AEs were observed. In Arm B, one (3%) patient achieved a complete response and one (3%) achieved a partial response; no responses were observed in Arms A and F. Nelistotug serum concentrations across doses were calculated to be sufficient to saturate the target in the tumor since >95% CD96 receptor occupancy was observed in peripheral blood immune cells. Conclusions: Nelistotug as monotherapy and in combination with dostarlimab and belrestotug had an acceptable safety and tolerability profile; however, efficacy was limited in this heavily pretreated patient population with advanced solid tumors.